Voltage-dependent potassium currents in hypertrophied rat astrocytes after a cortical stab wound - Anderová, Miroslava; Antonova, Tatiana; Petrík, David; Neprasová, Helena; Chvátal, Alexandr; Syková, Eva (Glia, 2004)
Changes in the membrane properties of reactive astrocytes in gliotic cortex induced by a stab wound were studied in brain slices of 21-28-day-old rats, using the patch-clamp technique and were correlated with changes in resting extracellular K+ concentration ([K+]e) measured in vivo using K+-selective microelectrodes. Based on K+ current expression, three types of astrocytes were identified in gliotic cortex: A1 astrocytes expressing a time- and voltage-independent K+ current component and additional inwardly rectifying K+ currents (K(IR)); A2 astrocytes expressing a time- and voltage-independent K+ current component and additional delayed outwardly rectifying K+ currents (K(DR)); and complex astrocytes expressing K(DR), K(IR), and A-type K+ (K(A)) currents and Na+ currents (I(Na)). Nestin/bromodeoxyuridine (BrdU)-negative A1 astrocytes were found further than approximately 100 microm from the stab wound and showed an upregulation of K(IR) currents within the first day post-injury (PI), correlating with an increased resting [K+]e. Their number declined from 62% of total astrocytes in control rats to 41% in rats at 7 days PI. Nestin/BrdU-positive A2 astrocytes were found only within a distance of approximately 100 microm from the stab wound and, in comparison to those in control rats, showed an upregulation of K(DR) currents. Their number increased from 8% of the total number of astrocytes in control rats to 39% 7 days PI. Both A1 and A2 astrocytes showed hypertrophied processes and increased GFAP staining, but an examination of cell morphology revealed greater changes in the surface/volume ratio in A2 astrocytes than in A1 astrocytes. Complex astrocytes did not display a hypertophied morphology; K(IR) currents in these cells were upregulated within 1 day PI, while the K(DR), K(A), and I(Na) currents were increased only 6 h PI. We conclude that two electrophysiologically, immunohistochemically, and morphologically distinct types of hypertrophied astrocytes are present at the site of a stab wound, depending on the distance from the lesion, and may have different functions in ionic homeostasis and/or regeneration.
Keywords: Membrane Potentials; Rats, Wistar; Wounds, Stab; Astrocytes; mozková kůra; potkani Wistar; hypertrofie; zvětšování buněk; Cell Enlargement; membránové potenciály; krysa rodu Rattus; Time Factors; Animals; zvířata; bodné rány; Rats; časové faktory; Hypertrophy; Potassium Channels, Voltage-Gated; astrocyty; draslíkové kanály řízené napětím; Cerebral Cortex